2014
DOI: 10.4049/jimmunol.1303226
|View full text |Cite
|
Sign up to set email alerts
|

Soluble HLA-I/Peptide Monomers Mediate Antigen-Specific CD8 T Cell Activation through Passive Peptide Exchange with Cell-Bound HLA-I Molecules

Abstract: Accumulating evidence that serum levels of soluble class I HLA molecules (sHLA-I) can, under various pathological conditions, correlate with disease stage and/or patient survival, has stimulated interest in defining whether sHLA-I can exert immunological functions. However, despite a mounting number of publications suggesting the ability of sHLA-I to affect immune effectors in vitro, the precise underlying mechanism still remains controversial. In this article, we address potential functions of both classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In our study, as a second finding, this was shown to be only partly true. Indeed, as already reported in scientific literature , regardless of the donation procedure lymphocytes are activated by the interaction with sHLA‐I molecules adsorbed plastic circuits during the procedure, acquiring a transient susceptibility to sHLA‐I biological effects such as transcriptional/post‐transcriptional TGF β 1 modulation and sFasL release. Nonetheless, our data do not deviate from the report that no increase of TGF β 1 is detectable in donors' plasma 24 h following plateletpheresis .…”
Section: Discussionmentioning
confidence: 68%
“…In our study, as a second finding, this was shown to be only partly true. Indeed, as already reported in scientific literature , regardless of the donation procedure lymphocytes are activated by the interaction with sHLA‐I molecules adsorbed plastic circuits during the procedure, acquiring a transient susceptibility to sHLA‐I biological effects such as transcriptional/post‐transcriptional TGF β 1 modulation and sFasL release. Nonetheless, our data do not deviate from the report that no increase of TGF β 1 is detectable in donors' plasma 24 h following plateletpheresis .…”
Section: Discussionmentioning
confidence: 68%
“…HLA in human is analogous to the MHC in other animals such as mouse. The classical HLA loci consist of class Ia (HLA-A, -B, -C), class Ib (HLA-E, -F, -G, -H), and class II (HLA-DR, -DQ, -DM, and -DP), which are involved in antigen presentation to CD8 + T cells, natural killer cells (NK cells), and CD4 + T cells, respectively (5, 6). They are encoded in a ~3,500 kb segment on human chromosome 6p21.3, which is the most variable region in the human genome (7) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the HLA region, also known as major histocompatibility complex (MHC), is located on the short arm of chromosome 6 (6p21.3) in humans, encoding the HLA class I (A, B and C) and class II (DR, DQ and DP) molecules (Allard et al ., ). A high level of molecule polymorphisms within the HLA region is characterised (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 97%